2023
DOI: 10.1093/ofid/ofad233
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review of the Prevalence of Long COVID

Abstract: Background Long Covid occurs in those infected with SARSCoV2 whose symptoms persist or develop beyond the acute phase. We conducted a systematic review to determine the prevalence of persistent symptoms, functional disability or pathological changes in adults or children at least 12 weeks post-infection. Methods We searched key registers and databases from 1st January 2020 to 2nd November 2021, limited to publications in Engl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(49 citation statements)
references
References 141 publications
1
48
0
Order By: Relevance
“…A lack of long-duration longitudinal/cohort studies is a contributory reason for this. A systematic review of long COVID prevalence in the general population noted a pooled estimate of prevalence between 13.6% and 43.9%, depending on definition and method of measurement 86. The review also noted increased prevalence in hospitalised patients 86.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A lack of long-duration longitudinal/cohort studies is a contributory reason for this. A systematic review of long COVID prevalence in the general population noted a pooled estimate of prevalence between 13.6% and 43.9%, depending on definition and method of measurement 86. The review also noted increased prevalence in hospitalised patients 86.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review of long COVID prevalence in the general population noted a pooled estimate of prevalence between 13.6% and 43.9%, depending on definition and method of measurement 86. The review also noted increased prevalence in hospitalised patients 86. Given the increased hospitalisation rates and poorer COVID-19 outcomes evident in PEI, long COVID burden in PEI is likely to be substantial.…”
Section: Discussionmentioning
confidence: 99%
“…With the lack of a consensus clinical definition of Long COVID, 20 assessment of the true accuracy of algorithms like ours is challenging. Moreover, the lack of a consistent estimate for Long COVID's prevalence 21 makes it difficult to determine an appropriate model threshold using real-world evidence. Assessing performance using the U09.9 label as ground truth is the most readily available option, but the inconsistency of the code's use by providers and its late availability 4 mean that many patients with Long COVID lack the label.…”
Section: Limitationsmentioning
confidence: 99%
“…51,69,70 Another systematic review found the risk difference (95% prediction intervals) for Long-COVID compared to controls was 13.9% (−16.2, 43.9), compared to controls in community-based samples 10.1% (−12.7, 32.8), and compared to controls in community-based samples assessed as at low risk of bias 4.8% (−13.2, 22.7). 71 Among COVID-19 cases, risk factors for Long-COVID in systematic reviews included female gender, 5,[7][8][9]41,42,45,72 dyspnea in the acute phase or asthma/chronic-lung-disease/ chronic-dyspnea, 5,41,42,72 previous psychiatric diagnosis (including prepandemic psychological distress), 5,8,41,72 severity of acute COVID-19 (including number of acute symptoms 42 and hospitalization, 7,42,43,72 especially in intensive care), 5,[7][8][9]42,43,72 and underlying comorbidity. 8,42,45,72 Individual studies have also emphasized psychiatric diagnoses as risk factors, for example, preexisting fibromyalgia, anxiety, depression, migraine, irritable bowel syndrome (IBS), eating disorder, or back pain; 50 and preexisting diagnosis of depression or anxiety.…”
Section: Table 2 (Continued)mentioning
confidence: 99%